A Children’s History of (Native) America: The Tales of Peter Parley, About America - Ocasion, Gina Marie (American Studies, 2017)
This essay considers the interpellation of children into U.S. national identity by way of Samuel Goodrich’s The Tales of Peter Parley, About America.I recognize a paradox of national identity wherein Indianness is both required for constructing an exceptional national character and calls attention to the ongoing crimes of cultural extermination, reaffirming the ways in which America is a settler colonial state.  While this tension between Indianness and Americanness has been brought to the surface in scholarship addressing adult culture, there is a curious absence in this conversation where children’s culture is concerned.